2021
DOI: 10.1136/neurintsurg-2020-017017
|View full text |Cite
|
Sign up to set email alerts
|

Quantified health and cost effects of faster endovascular treatment for large vessel ischemic stroke patients in the Netherlands

Abstract: BackgroundThe effectiveness of endovascular treatment (EVT) for large vessel occlusion (LVO) stroke severely depends on time to treatment. However, it remains unclear what the value of faster treatment is in the years after index stroke. The aim of this study was to quantify the value of faster EVT in terms of health and healthcare costs for the Dutch LVO stroke population.MethodsA Markov model was used to simulate 5-year follow-up functional outcome, measured with the modified Rankin Scale (mRS), of 69-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…The 5-year follow-up period was chosen based on the availability of cohorts for evaluating the forecasted mRS up to 5 years. 14 Moreover, simulating effects beyond 5 years would introduce an exponentially increasing error in the mRS forecasts which becomes even more prominent due to the high baseline age (median MR CLEAN-NO IV cohort included in CLEOPATRA: 71 (IQR 61–79) years old) and concurrent relatively short life expectancy of the selected population. The model will exist of a short-term part simulating mRS at 90 days and a long-term part simulating the yearly mRS decay.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 5-year follow-up period was chosen based on the availability of cohorts for evaluating the forecasted mRS up to 5 years. 14 Moreover, simulating effects beyond 5 years would introduce an exponentially increasing error in the mRS forecasts which becomes even more prominent due to the high baseline age (median MR CLEAN-NO IV cohort included in CLEOPATRA: 71 (IQR 61–79) years old) and concurrent relatively short life expectancy of the selected population. The model will exist of a short-term part simulating mRS at 90 days and a long-term part simulating the yearly mRS decay.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to our previous work, mRS subscores will be used as health states with related costs and QALYs per unit of time per health state. 14 Cohorts will be simulated based on patient-level micro-simulations to relate baseline characteristics to cost-effectiveness outcomes. The health state transition model is depicted in Figure 1.…”
Section: Model Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we reported a wide variety of sensitivity differences as the current evidence comparing NCCT+CTA+CTP with NCCT+CTA based LVO detection is limited by a small sample size and suboptimal research designs (1)(2)(3)(4). Third, we used conservative ORs for the EVT treatment effect based on the MR CLEAN trial (12). In recent years, EVT workflows have improved, improving the treatment effect of EVT (24).…”
Section: Probabilistic Sensitivity Analysismentioning
confidence: 99%